Strange bedfellows: Federal systems and performance management. Issue 4 (8th August 2019) - Jones, Stephen; Bouckaert, Geert; Fafard, Patrick; Bernier, Luc
ABSTRACT: This paper offers the first link between models of the measurement and management of performance and the dimensions of governance arrangements in federal systems. Four ideal type approaches to governance in federal systems are correlated against four ideal types of measuring and managing performance. The paper develops a model that will support empirical research examining reform trajectories where evolving systems of federalism require evolving systems to manage performance in joint arrangements between levels of government.